Responses of Plants to Environmental Stresses - Szymańska, Renata (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Environmental abiotic stresses, such as extreme temperatures, drought, excess light, salinity, and nutrient deficiency, have detrimental effects on plant growth, development, and yield. Plants are equipped with various adaptation mechanisms to cope with such unfavorable conditions. Our understanding of plants' abiotic stress responses is crucial to maintaining efficient plant productivity. This book on the responses of plants to environmental stresses is an attempt to find answers to several basic questions related to their adaptation and protective mechanisms against abiotic stresses. The following chapters of the book describe examples of plants' protective strategies, which cover physiological, cellular, biochemical, and genomic mechanisms. This book is aimed for use by advanced students and researchers in the area of stress biology, plant molecular biology and physiology, agriculture, biochemistry, as well as environmental sciences.